2023
DOI: 10.3390/rs15194886
|View full text |Cite
|
Sign up to set email alerts
|

Retrievals of Chlorophyll-a from GOCI and GOCI-II Data in Optically Complex Lakes

Yuyu Guo,
Xiaoqi Wei,
Zehui Huang
et al.

Abstract: The chlorophyll-a (Chla) concentration is a key parameter to evaluate the eutrophication conditions of water, which is very important for monitoring algal blooms. Although Geostationary Ocean Color Imager (GOCI) has been widely used in Chla inversion, the consistency of the Rayleigh-corrected reflectance (Rrc) of GOCI and GOCI-II sensors still needs to be further evaluated, and a model suitable for lakes with complex optical properties needs to be constructed. The results show that (1) the derived Chla values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Simulated hyperspectral 𝑅 𝑟𝑠 (𝜆) facilitate the construction of more accurate Chla estimation models for optically complex turbid inland waters. [142] compared the performance of different Chla algorithms for GOCI and GOCI-II in Lake Taihu, Lake Chaohu, and Lake Hongze with 𝐿 𝑟𝑐 (𝜆) as input. The results indicated that the RF algorithm outperformed the commonly used spectral index models.…”
Section: Chlamentioning
confidence: 99%
“…Simulated hyperspectral 𝑅 𝑟𝑠 (𝜆) facilitate the construction of more accurate Chla estimation models for optically complex turbid inland waters. [142] compared the performance of different Chla algorithms for GOCI and GOCI-II in Lake Taihu, Lake Chaohu, and Lake Hongze with 𝐿 𝑟𝑐 (𝜆) as input. The results indicated that the RF algorithm outperformed the commonly used spectral index models.…”
Section: Chlamentioning
confidence: 99%
“…Simulated hyperspectral R rs (λ) facilitate the construction of more accurate Chla estimation models for optically complex turbid inland waters. Guo [141] compared the performance of different Chla algorithms for the GOCI and the GOCI-II in Lake Taihu, Lake Chaohu, and Lake Hongze, with L rc (λ) as input. The results indicated that the RF algorithm outperformed the commonly used spectral index models.…”
Section: Chlamentioning
confidence: 99%
“…Along with certain agricultural practices, domestic and industrial wastewater discharge are identi ed as the main sources of this eutrophication (Converse 1995 Currently, due to the vastness, remoteness, and di culty of accessing certain wetland areas, groundbased monitoring methods have become expensive, costly, and often unfeasible. Due to the ease of acquisition and rapid processing of images (Guo et al 2023), remote sensing techniques based on satellite imagery have become indispensable for monitoring water quality parameters, including chlorophyll-a and water transparency (Mishra and Mishra 2012); (Alikas and Kratzer 2017). Several multispectral satellites have been launched, including Landsat series data, MODIS data, and MERIS data.…”
Section: Introductionmentioning
confidence: 99%